PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KOMITMEN ORGANISASI STUDI KASUS PADA HOTEL DOUBLETREE BY HILTON JAKARTA DIPONEGORO - Pamuji Gesang Raharjo; Ikhsan Iraldi Wicaksana (Human Capital Development, 2018)
Purpose- This study aims to determine the effect of leadership, organizational culture and motivation on organizational commitment at Doubletree By Hilton Hotel Jakarta. Design/methology/approach- In this study, the authors conducted a survey by distributing questionnaires to employees of the Doubletree By Hilton Hotel Jakarta. The number of samples in this study were 160 employees obtained by using random non-random sampling techniques. Findings- The results of the study show the three variables jointly influence organizational commitment at Doubletree By Hilton Hotel Jakarta. By using the t test, it was found that leadership had a significant influence on increasing organizational commitment at Doubletree By Hilton Hotel Jakarta is 5.83%, while organizational culture has a significant influence on increasing organizational commitment is 32.90%, while in the motivation variable also effect on increasing organizational commitment amounted to 6.86%. If all three variables are simultaneously found the ability of the three variables to explain organizational commitment is 80.40%, other factors of 19.60% are not discussed in this study, including work environment, compensation and other things. Research limitations- But the capacity of independent leadership variables to influence the effect on organizational commitment is weaker than other variables, which are not included in this study.Practical implications- Human resource managers must maintain authentic information through available organizational communications. Apart from that it is the main area for evaluating existing leadership because it has a greater effect on organizational commitment.